Luminous Type II Short-Plateau Supernovae 2006Y, 2006ai, and 2016egz: A Transitional Class from Stripped Massive Red Supergiants - Hiramatsu Daichi; Howell D Andrew; Moriya Takashi J; Goldberg Jared A; Hosseinzadeh Griffin; Arcavi Iair; Anderson Joseph P; Gutíerrez Claudia P; Burke Jamison; McCully Curtis; Valenti Stefano; Galbany Lluís; et al. (IOP PUBLISHING LTD, 2025)
The diversity of Type II supernovae (SNe II) is thought to be driven mainly by differences in their progenitor's hydrogen-rich (H-rich) envelope mass, with SNe IIP having long plateaus (similar to 100 days) and the most massive H-rich envelopes. However, it is an ongoing mystery why SNe II with short plateaus (tens of days) are rarely seen. Here, we present optical/near-infrared photometric and spectroscopic observations of luminous Type II short-plateau SNe 2006Y, 2006ai, and 2016egz. Their plateaus of about 50-70 days and luminous optical peaks (less than or similar to-18.4 mag) indicate significant pre-explosion mass loss resulting in partially stripped H-rich envelopes and early circumstellar material (CSM) interaction. We compute a large grid of MESA+STELLA single-star progenitor and light-curve models with various progenitor zero-age main-sequence (ZAMS) masses, mass-loss efficiencies, explosion energies, Ni-56 masses, and CSM densities. Our model grid shows a continuous population of SNe IIP-IIL-IIb-like light-curve morphology in descending order of H-rich envelope mass. With large Ni-56 masses (greater than or similar to 0.05M(circle dot)), short-plateau SNe II lie in a confined parameter space as a transitional class between SNe IIL and IIb. For SNe 2006Y, 2006ai, and 2016egz, our findings suggest high-mass red supergiant (RSG) progenitors (M-ZAMS similar or equal to 18-22M(circle dot)) with small H-rich envelope masses (M-Henv similar or equal to 1.7 M-circle dot) that have experienced enhanced mass loss (M similar or equal to 10(-2) M-circle dot yr(-1)) for the last few decades before the explosion. If high-mass RSGs result in rare short-plateau SNe II, then these events might ease some of the apparent underrepresentation of higher-luminosity RSGs in observed SN II progenitor samples.